Performing place, practising memories: Aboriginal Australians, hippies and the state - Henry, Rosita (Space and place, 2012)
During the 1970s a wave of 'counter-culture' people moved into rural communities in many parts of Australia. This study focuses in particular on the town of Kuranda in North Queensland and the relationship between the settlers and the local Aboriginal population, concentrating on a number of linked social dramas that portrayed the use of both public and private space. Through their public performances and in their everyday spatial encounters, these people resisted the bureaucratic state but, in the process, they also contributed to the cultivation and propagation of state effects.